2019
DOI: 10.1177/2047487319839162
|View full text |Cite
|
Sign up to set email alerts
|

Association of central blood pressure with left atrial structural and functional abnormalities in hypertensive patients: Implications for atrial fibrillation prevention

Abstract: Aims Functional and structural abnormalities of the left atrium have been demonstrated to be clinically and prognostically significant in a range of cardiovascular disorders, increasing the risk of atrial fibrillation. Among the potential contributors to these aberrations, central arterial factors remain insufficiently defined. Accordingly, we sought to investigate the determinants of left atrium abnormalities in hypertension, with special focus on central haemodynamics. Methods In this retrospective, cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Impairment in GLS represents the first step in the cascade of LV remodeling in the natural history of HHD, and may parallel or even precede other clinical forms of myocardial affection such as LV hypertrophy, diastolic dysfunction, or left atrial structural and functional abnormalities. [37][38][39][40][41][42] Conversely, LV circumferential performance deteriorates in more advanced stages of the disease, and may even increase the asymptomatic phase of heart failure (stage B) to compensate for the dysfunction in the longitudinal direction. 10,[43][44][45][46][47][48] This paper demonstrated that changes in LV longitudinal systolic deformation over follow-up were associated with alterations in relevant LV afterload-associated indices, among which central augmentation pressure remained an independent predictor after multivariable adjustments for possible confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in GLS represents the first step in the cascade of LV remodeling in the natural history of HHD, and may parallel or even precede other clinical forms of myocardial affection such as LV hypertrophy, diastolic dysfunction, or left atrial structural and functional abnormalities. [37][38][39][40][41][42] Conversely, LV circumferential performance deteriorates in more advanced stages of the disease, and may even increase the asymptomatic phase of heart failure (stage B) to compensate for the dysfunction in the longitudinal direction. 10,[43][44][45][46][47][48] This paper demonstrated that changes in LV longitudinal systolic deformation over follow-up were associated with alterations in relevant LV afterload-associated indices, among which central augmentation pressure remained an independent predictor after multivariable adjustments for possible confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of treatment heterogeneity patterns across systems could also benefit from a quantification of risk to understand how treatments vary across both a system and a spectrum of risk. Clinical risk scores such as Admit-AF might also be integrated with other diagnostic modalities (such as hemodynamic and imaging data) 13 to develop a more robust picture of a patient's condition which may result in more accurate models.…”
mentioning
confidence: 99%
“…In the current edition of the journal, Przewlocka-Kosmala et al. 12 nicely report the correlation between increased central blood pressure and left atrium structural and functional abnormalities. With respect to pulse pressure, central blood pressure should be less dependent on large arteries’ stiffness than on peripheral haemodynamics.…”
mentioning
confidence: 99%
“…In their work, Przewlocka-Kosmala et al. 12 add another element to the complex landscape of cardiac pathophysiology, by stressing the relationship between left atrium reservoir function and LV afterload. Large peripheral arteries might be abnormal for different reasons and can impact on the heart in different ways.…”
mentioning
confidence: 99%
See 1 more Smart Citation